Triapine Radiochemotherapy in Advanced Stage Cervical Cancer - Kunos, Charles A.; Ivy, S. Percy (Frontiers in Oncology, 2018)
Clinical ribonucleotide reductase inhibitors have reinvigorated enthusiasm for radiochemotherapy treatment of patients with regionally advanced stage cervical cancers. About two-thirds of patients outlive their cervical cancer (Rose et al., 2007), even though up to half of their tumors retain residual microscopic disease (Stehman et al., 2007). The National Cancer Institute (NCI) Cancer Therapy Evaluation Program (CTEP) conducted two prospective trials of triapine-cisplatin-radiation to improve upon this finding by precisely targeting cervical cancer’s overactive ribonucleotide reductase. Triapine’s potent inactivation of ribonucleotide reductase arrests cells at the G1/S cell cycle restriction checkpoint and enhances cisplatin-radiation cytotoxicity. In this article, we provide perspective on challenges encountered in and future potential of clinical development of a triapine-cisplatin-radiation combination for patients with regionally advanced cervical cancer. New trial results and review presented here suggest that a triapine-cisplatin-radiation combination may offer molecular cell cycle target control to maximize damage in cancers and to minimize injury to normal cells. A randomized trial now accrues patients with regionally advanced stage cervical cancer to evaluate triapine’s contribution to clinical benefit after cisplatin-radiation (clinicaltrials.gov, NCT02466971).